World experience in the development of auditing activities in Uzbekistan - Nuriddinova Shakhnoza Toirovna (Periodica Journal, 2022)
This article deals with the provisions of international auditing standards, the conceptual basis of international auditing standards, and the structure of international auditing standards
Keywords: Association; auditing; International; Federation